Potentials of the Rotary Cutting Process for Electrical Steel Strip - Ziegler, Marco; Schneider, Michael; Hubert, Markus; Franke, Jörg (2018 8th International Electric Drives Production Conference, EDPC 2018 - Proceedings, 2018)
To minimize eddy current losses, stators and rotors are traditionally designed laminated. For this purpose, the single sheets are electrically separated from each other by an insulation layer. The production of electrical steel laminations for rotor and stator stacks is divided into the steps of cutting, stacking and joining. Currently, there are several possibilities for each process step. The selection of the suitable process depends on the application, quantity and size of the electrical steel laminations. In mass production, the electrical steel strip is separated mainly by stamping. In prototype manufacturing and for small series, the lamination is cut out by laser. In addition, wire EDM and water-jet cutting are applied in specific applications. Rotary cutting of electrical steel strip is a process that is not yet used in industry. However, the novel approach has a great potential, since investment and tooling costs are relatively low. Furthermore, the process is suitable for the production of thin laminations (smaller than 0.3 mm) which are used in traction motors for electric vehicles.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Electrical Steel Processing; Laser Cutting; Rotary Cutting; Stamping